2013
DOI: 10.1177/1044207313502538
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Defining the Activities of Participant Direction Programs

Abstract: Nearly 11 million Americans, half of which are nonelderly, need long-term supports and services (Kaye, Harrington, & LaPlante, 2010), including personal assistance services, home and community-based services, and institutional services (Ng, Harrington, & Kitchener, 2010). The paid supports and services these individuals receive are funded primarily through Medicaid and are traditionally provided through agency direction models that provide little opportunity for participant decision-making regarding the servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition, considering the catalyst for choosing to participant direct the supports and services for adults with SIDD was directly related to the achievement of desired outcomes for the adult, an important question for future research would entail examining the barriers to accomplishing desired outcomes using agency-directed services. The respondents in this study had full employer and budget authority, which is not available in all programs of participant direction (Gross, 2010; Nadash & Crisp, 2005; National Council on Disability, 2004; Tritz, 2005). A study comparing outcomes for adults with SIDD across sites with different levels of authority to participant direct may provide even greater detail regarding what components of participant direction (i.e., hiring and managing service providers, allocating monies for services) actually facilitate accomplishment of improved quality of life outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, considering the catalyst for choosing to participant direct the supports and services for adults with SIDD was directly related to the achievement of desired outcomes for the adult, an important question for future research would entail examining the barriers to accomplishing desired outcomes using agency-directed services. The respondents in this study had full employer and budget authority, which is not available in all programs of participant direction (Gross, 2010; Nadash & Crisp, 2005; National Council on Disability, 2004; Tritz, 2005). A study comparing outcomes for adults with SIDD across sites with different levels of authority to participant direct may provide even greater detail regarding what components of participant direction (i.e., hiring and managing service providers, allocating monies for services) actually facilitate accomplishment of improved quality of life outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although consumers have increasingly received services in their homes or communities for the past few decades, the services have traditionally been agency directed. In agency-directed programs, the individual with a disability typically has little choice (“the act of making a selection from a range of options”; Gross, 2010, p. 3) or control (act of “making substantive decisions” and “taking responsibility” for them; Gross, 2010, p. 4) over the services received or who provides them (Doty, Mahoney, & Simon-Rusinowitz, 2007). More recently, however, ever-increasing numbers of states have begun offering adults with IDD or their surrogate decision makers (i.e., parents, guardians, other family members, friends) the opportunity to participant-direct the HCBS waiver supports and services of the adult (Breihan, 2007; Walker, Hewitt, Bogenschultz, & Hall-Lande, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals and families who self-direct often pay higher hourly wages to DSPs, trading fewer hours of support for more dependable and longer lasting relationships with DSPs, and sometimes not offering certain benefits to DSPs who prefer compensation in the form of higher pay. As a result, studies have shown that self-directed models involve lower rates of DSP turnover (Gross et al, 2015;Timberlake et al, 2014). Using self-direction allows individuals and their families to more easily integrate the natural support of family and friends, and it is sometimes easier to arrange intermittent or temporary supports when they are needed because of the program flexibility (Melda et al, 2009).…”
Section: Systemic Expansion Of a Pipeline Of Direct Support Professio...mentioning
confidence: 99%